Transitional justice, peace and accountability : outreach and the role of international courts after conflict - Lincoln, Jessica (London : Routledge, 2011)
'The book looks at the outreach and communication strategies employed by internationalised courts to try to understand the wider impact of international justice. This book critically examines the role of outreach within international justice focusing specifically on the role of outreach at the Special Court for Sierra Leone (SCSL). It contributes to understanding of the relationship between international courts and the affected populations; an area currently underexplored and little understood. The assumption that justice brings peace underpins much of the thinking, and indeed action, of international justice, yet little is known if this is actually the case. Significant questions surrounding the link between peace and justice remain: do trials deter would-be war criminals; is justice possible for the most heinous crimes; can international justice replace local justice? This book explores these questions in relation to recent developments in international justice that have both informed and shaped the creation of the hybrid tribunal in Sierra Leone. Through empirical analysis, Transitional Justice, Peace and Accountability, answers these questions and provides an insight into individual and community perceptions of international justice.This book will be of much interest to students of transitional justice, war crimes, peace and conflict studies, human rights, international law, and IR in general'--
'The book looks at the outreach and communication strategies employed by internationalised courts to try to understand the wider impact of international justice'--
Includes bibliographical references (p. 169-183) and index.
Keywords: Special Court for Sierra Leone; Transitional justice -- Sierra Leone; International criminal courts -- Sierra Leone